E-Government and Transparency: Strategies to Increase Government Accountability in the Digital Era - Irwan Gesmi; Maal Abrar (Doctoral Program of Social Science Pasundan University, 2026)
This study aims to examine the role of e-government in enhancing transparency and accountability in public governance. The research hypothesizes that e-government has a significant positive effect on transparency and accountability, and that transparency mediates the relationship between e-government and accountability. This study employs a quantitative explanatory research design using a cross-sectional approach. Data were collected from 180 respondents who have experience using e-government services in Indonesia, selected through purposive sampling. The data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The variables examined include e-government, transparency, and accountability, measured using validated indicators and Likert-scale questionnaires. The results show that e-government has a significant positive effect on transparency (? = 0.754; p < .001) and accountability (? = 0.782; p < .001), while transparency also significantly influences accountability (? = 0.468; p < .001), confirming its mediating role. These findings indicate that the implementation of e-government enhances public information accessibility and strengthens accountability mechanisms. The implications of this study suggest that governments should strengthen digital governance strategies by improving infrastructure, promoting open data initiatives, and enhancing digital literacy to ensure effective and inclusive public services. This study contributes to the digital governance literature by integrating technological and institutional perspectives. The article includes 20 references, 4 tables, 4 figures, and a structured questionnaire as the research instrument.